2012
DOI: 10.1016/j.advwatres.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Two-source energy balance model estimates of evapotranspiration using component and composite surface temperatures

Abstract: The two source energy balance model (TSEB) can estimate evaporation (E), transpiration (T), and evapotranspiration (ET) of vegetated surfaces, which has important applications in water resources management for irrigated crops. The TSEB requires soil (T S) and canopy (T C) surface temperatures to solve the energy budgets of these layers separately. Operationally, usually only composite surface temperature (T R) measurements are available at a single view angle. For surfaces with nonrandom spatial distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 70 publications
11
143
0
2
Order By: Relevance
“…Prior inter-comparisons showed that in general flux estimates by the TSEB model are in better agreement with EC measurements over a wide range of environmental conditions and over homogeneous landscapes compared to contextual models (Choi et al 2009; French, Hunsaker, and Thorp 2015; Timmermans et al 2007; Xia et al 2015; Colaizzi et al 2012; Li et al 2005). The slightly higher error statistics of the TSEB model in this study compared to the contextual models are a consequence of the larger deviations of the model results from the observations for the two flights on 6 July, a day with scattered clouds, as discussed above in detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior inter-comparisons showed that in general flux estimates by the TSEB model are in better agreement with EC measurements over a wide range of environmental conditions and over homogeneous landscapes compared to contextual models (Choi et al 2009; French, Hunsaker, and Thorp 2015; Timmermans et al 2007; Xia et al 2015; Colaizzi et al 2012; Li et al 2005). The slightly higher error statistics of the TSEB model in this study compared to the contextual models are a consequence of the larger deviations of the model results from the observations for the two flights on 6 July, a day with scattered clouds, as discussed above in detail.…”
Section: Resultsmentioning
confidence: 99%
“…The roughness lengths for momentum and heat required for the estimation of the resistances were set to 0.125 of the vegetation height. The series resistance network is described in Colaizzi et al (2012), Kustas and Norman (1999), and Timmermans et al (2007). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such frameworks use as input data either the component surface temperatures (e.g. soil and vegetation components retrieved from directional surface temperature data; Jia et al, 2003, or Colaizzi et al, 2012 or a single soilvegetation composite surface skin temperature. For the former, there is no current operational satellite that offers estimates of temperatures at two contrasted view angles with a very small interval between both acquisitions, even though the soon to be launched Sentinel-3 mission will have such capability (Donlon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst them, one can mention the development of a more complex net radiation scheme, with an initialization of soil and vegetation temperatures in separate formulations of the net radiation of the soil and the canopy or the use of an incremental decrease in a transpiration efficiency (Kustas and Norman, 1999; it corresponds roughly to the ratio between the actual and potential transpiration rates and matches the definition of the efficiency used in the present work). The TSEB rationale has been translated into several algorithms, with the possibility of using directional radiative temperatures (Kustas and Norman, 1997), day-night temperature difference (Guzinski et al, 2013; Nor- , correcting for clumping effects in sparsely vegetated areas (Anderson et al, 2005), and finally by taking into account a Penman-Monteith formulation for potential transpiration (Colaizzi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%